2020
DOI: 10.3389/fnins.2020.00074
|View full text |Cite
|
Sign up to set email alerts
|

Lipids in the Physiopathology of Hereditary Spastic Paraplegias

Abstract: Hereditary spastic paraplegias (HSP) are a group of neurodegenerative diseases sharing spasticity in lower limbs as common symptom. There is a large clinical variability in the presentation of patients, partly underlined by the large genetic heterogeneity, with more than 60 genes responsible for HSP. Despite this large heterogeneity, the proteins with known function are supposed to be involved in a limited number of cellular compartments such as shaping of the endoplasmic reticulum or endolysosomal function. Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 206 publications
(246 reference statements)
2
33
0
Order By: Relevance
“…Disrupted ER, on which LDs form, and decreased Drp1 levels may therefore synergistically contribute to neurodegeneration in our model of HSP by disrupting LD formation. Interestingly, defects in lipid metabolism and storage within LDs are increasingly being associated with HSPs suggesting that lipid biogenesis may contribute to the pathophysiology of these diseases [64].…”
Section: Discussionmentioning
confidence: 99%
“…Disrupted ER, on which LDs form, and decreased Drp1 levels may therefore synergistically contribute to neurodegeneration in our model of HSP by disrupting LD formation. Interestingly, defects in lipid metabolism and storage within LDs are increasingly being associated with HSPs suggesting that lipid biogenesis may contribute to the pathophysiology of these diseases [64].…”
Section: Discussionmentioning
confidence: 99%
“…The extreme polarization of cortical motor neurons makes them vulnerable to even minor disturbances of a plethora of pathways. Disruption or abnormalities of endosomal trafficking and dynamics, mitochondrial quality control, endoplasmic reticulum (ER) morphogenesis, cargo-mediated transport on the microtubules, lysosomal function, and lipid metabolism play a role in the pathogenesis of HSP ( Blackstone et al, 2011 ; Rugarli and Langer, 2012 ; Allison et al, 2017 ; Blackstone, 2018a ; Darios et al, 2020 ). Here, we focus on the intriguing connection between several HSP proteins and the biology of lipid droplets, and discuss the possible role of LD dysfunction in the pathogenesis of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Although little is known about the mechanisms related to neurodegeneration in complicated forms, the functional studies carried out in recent years on HSP-linked genes have suggested that alterations of intracellular trafficking may be a common element. The affected cellular functions include lipid metabolism, active axonal transport, organelle shaping, and the endo-lysosomal system ( Boutry et al, 2019a ; Darios et al, 2020 ; Öztürk et al, 2020 ). Although the progress made in deciphering the pathological process underlying HSP, there is still no specific cure to prevent or slow down neuronal degeneration or dysfunction.…”
Section: Introductionmentioning
confidence: 99%